2018
DOI: 10.1002/path.5183
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the spatiotemporal genetic heterogeneity in metastatic lung adenocarcinoma using a nuclei flow‐sorting approach

Abstract: Variable tumor cellularity can limit sensitivity and precision in comparative genomics because differences in tumor content can result in misclassifying truncal mutations as region‐specific private mutations in stroma‐rich regions, especially when studying tissue specimens of mediocre tumor cellularity such as lung adenocarcinomas (LUADs). To address this issue, we refined a nuclei flow‐sorting approach by sorting nuclei based on ploidy and the LUAD lineage marker thyroid transcription factor 1 and applied thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 57 publications
(52 reference statements)
5
11
0
Order By: Relevance
“…Our gene copy number data suggest persistent genomic instability as chromosomal aberrations are detected even after branching of the two components. The high overall concordance between the chromosomal copy number aberrations profiles of the components support our previous data from metastatic LUAD showing that most aberrant genomic events are truncal with only limited heterogeneity between primary tumors and matched metastases [34]. Nevertheless, the two ASC components had private CNVs, which were similar to the CNVs known to be typical for their pure morphological counterparts, i.e.…”
Section: Discussionsupporting
confidence: 82%
“…Our gene copy number data suggest persistent genomic instability as chromosomal aberrations are detected even after branching of the two components. The high overall concordance between the chromosomal copy number aberrations profiles of the components support our previous data from metastatic LUAD showing that most aberrant genomic events are truncal with only limited heterogeneity between primary tumors and matched metastases [34]. Nevertheless, the two ASC components had private CNVs, which were similar to the CNVs known to be typical for their pure morphological counterparts, i.e.…”
Section: Discussionsupporting
confidence: 82%
“…The total ctDNA represented in the body fluid is a sum of the tumor localization, phenotype and differentiation grade. Tumor samples with less than 10% neoplastic cell content may lose the low rate of genetic aberration sensitivity (Lorber et al, 2019;Méhes, 2019;Schwarzenbach et al, 2011). Therefore, the ctDNA concentration is not controllable, as tumor composition and localization are major preanalytical variables.…”
Section: The "Bottle Neck" Of Ctdna Analysismentioning
confidence: 99%
“…Nuclei isolation from FF and FFPE samples was conducted as described previously (9)(10)(11)(12). All nuclei were DAPI stained for sorting, DNA quantification and ploidy analysis.…”
Section: Nuclei Isolation and Multiparameter Flow-sortingmentioning
confidence: 99%
“…Molecular profiling of LUSC is further challenged by the often low tumor cell content of LUSC tissue (8). To overcome this hurdle, we previously showed that the tumor purity of LUAD can be greatly enhanced by an advanced nuclei flow-sorting technique (9). Briefly, cells were stained with 4',6-Diamin-2-phenylindol (DAPI) and an antibody for TTF-1 to isolate LUAD specific cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation